1993
DOI: 10.1210/jcem.76.4.8473373
|View full text |Cite
|
Sign up to set email alerts
|

Remission of subclinical adrenocortical failure in subjects with adrenal autoantibodies.

Abstract: Idiopathic Addison's disease is a chronic organ-specific autoimmune disorder with a long subclinical period characterized only by the presence of adrenal autoantibodies (AA) with or without adrenal function failure. The aim of this longitudinal study was to evaluate the behavior of AA using, an indirect fluorescence method, and adrenal function in 20 AA-positive and 50 AA-negative patients screened by an investigation of a large population of organ-specific autoimmune disease patients without clinical Addison'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 16 publications
4
58
1
6
Order By: Relevance
“…After several months or years, a dysfunction of the zona fasciculata becomes evident which is manifested at first by a decrease of the plasma cortisol response to adrenocorticotropic hormone (ACTH) (stage 2), followed by an increased plasma ACTH level (stage 3) and finally by a decreased plasma cortisol level and overt clinical symptoms (stage 4) (34). Subsequently, it has been reported that ACA in some patients without clinical AAD can disappear spontaneously or after corticosteroid therapy with restoration of the previous impaired adrenal function (35). However, recent follow-up studies of 58 ACA-positive patients (children and adults) indicated that ACA were persistent markers of progression towards overt or subclinical AAD (31,32).…”
Section: Aca In Patients Without Clinical Aadmentioning
confidence: 99%
See 2 more Smart Citations
“…After several months or years, a dysfunction of the zona fasciculata becomes evident which is manifested at first by a decrease of the plasma cortisol response to adrenocorticotropic hormone (ACTH) (stage 2), followed by an increased plasma ACTH level (stage 3) and finally by a decreased plasma cortisol level and overt clinical symptoms (stage 4) (34). Subsequently, it has been reported that ACA in some patients without clinical AAD can disappear spontaneously or after corticosteroid therapy with restoration of the previous impaired adrenal function (35). However, recent follow-up studies of 58 ACA-positive patients (children and adults) indicated that ACA were persistent markers of progression towards overt or subclinical AAD (31,32).…”
Section: Aca In Patients Without Clinical Aadmentioning
confidence: 99%
“…Recently, the laboratory diagnosis of AAD has been enriched by use of specific recombinant autoantigens. Two different immunoprecipitation assays for the detection of autoantibodies to 21-OH (21-OH Abs) have been developed, one based on 35 S-labeled 21-OH produced in an in vitro transcriptiontranslation system (56,70), the other based on 125 Ilabeled recombinant 21-OH produced in yeast (59). Immunoprecipitation assays based on 35 S-21-OH are highly specific and sensitive with a good reproducibility but there are limitations associated with the use of DNA and 35 S-labeled material.…”
Section: New Tests For Adrenal Autoantibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescein isothiocyanate-conjugated rabbit antihuman immunoglobulin G (IgG) serum (Dako, Milan, Italy) diluted 1:40, was used to detect the presence of ACA reacting with adrenal antigens. Complement-fixing ACA were detected with rabbit fluorescein isothiocyanate serum antihuman C3 (Dako) at a 1:40 dilution as previously described (6). Activated partial thromboplastin time was prolonged and did not normalize after the addition of normal plasma thus revealing that it was not caused by insufficient and/or altered production of coagulation factors.…”
Section: Case Reportmentioning
confidence: 99%
“…ACA are regarded as sensitive markers of the autoimmune form of adrenal failure (6,14). Although their role in the primary pathogenic response is unclear, it is likely that they arise as a consequence of T-cell-mediated tissue damage, which seems to be a major event in the pathogenesis of adrenal failure.…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%